2021
DOI: 10.3389/fcell.2021.661486
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cells Promote Myelin Formation and Elimination

Abstract: Building a functional nervous system requires the coordinated actions of many glial cells. In the vertebrate central nervous system (CNS), oligodendrocytes myelinate neuronal axons to increase conduction velocity and provide trophic support. Myelination can be modified by local signaling at the axon-myelin interface, potentially adapting sheaths to support the metabolic needs and physiology of individual neurons. However, neurons and oligodendrocytes are not wholly responsible for crafting the myelination patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 219 publications
1
18
0
Order By: Relevance
“…The axo-myelin interaction is so close that, by itself, it constitutes a functional unit with a complex and deeply intermingled physiology. However, both astrocytes and microglia interact with axo-myelin units and influence their function[ 176 - 179 ]. Metabolic homeostasis and de novo formation or plasticity of myelin internodes and nodes of Ranvier are modulated by astrocytes and microglia.…”
Section: Perspectives: Myelination Is Not An Exclusive Oligodendrogli...mentioning
confidence: 99%
“…The axo-myelin interaction is so close that, by itself, it constitutes a functional unit with a complex and deeply intermingled physiology. However, both astrocytes and microglia interact with axo-myelin units and influence their function[ 176 - 179 ]. Metabolic homeostasis and de novo formation or plasticity of myelin internodes and nodes of Ranvier are modulated by astrocytes and microglia.…”
Section: Perspectives: Myelination Is Not An Exclusive Oligodendrogli...mentioning
confidence: 99%
“…Recent studies have shown that the complex interconnections between glial cells and immune cells play a crucial role in the maintenance of CNS homeostasis, inflammation, and neuropathic pain 19 . Astrocytes reversibly regulate the demyelination and remyelination of myelinated nerve fibers during nerve injury by secreting different cytokines 20 . CCL2 and CXCL10, which are produced by reactive astrocytes, can recruit lymphocytes in the peripheral blood to the CNS, and astrocytes provide nutritional support for these infiltrating immune cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…FGF2, via the acti-vation of the extracellular signal-related kinase (ERK) 1/2, targets the transcription factor Myrf, in addition to activating the mechanistic target of rapamycin complex 1 (mTORC1) in the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/mTOR pathway [45]. The variability of myelin is also dependent on other glial cells, i.e., astrocytes, microglia, and cell types of the vasculature, by providing materials for myelin building and promoting the differentiation of oligodendrocytes [46].…”
Section: Oligodendrocyte Differentiation Maturation and Myelinationmentioning
confidence: 99%